The effect of the EU ETS on emissions of Swedish industries - Åberg, Stina (2021)
Industries globally produced 50% of total CO₂ emissions in 2018, largely contributing to current climate changes. The efficiency of environmental policies is crucial for reaching necessary abatement goals. The EU ETS policy covers the most emission intensive industries, whereas it is imperative to repeatedly evaluate the policy efficiency. There is yet no consensus whether the price of EU ETS CO₂ allowances affects the emissions. Using a panel data regression analysis, this thesis examined the effect of the EU ETS allowance price on emissions of various Swedish industries. Overall, the results showed all independent variables to be statistically significant. The model estimated that a 1% increase in price is associated with a 12,73% decrease in emissions. However, the model contains certain limitations which may have caused biased results, hence the results should be interpreted with caution. The graphical analysis showed indications that all sectors except Iron & Steel has decreased their overall emissions and become more environmentally friendly due to the EU ETS carbon price. From these results, the study concludes that the allowance price of the EU ETS has a significant negative effect on the emissions of Swedish industries. It also concludes that the efficiency of the policy seems to vary among the different sectors, thus sector-specific adjustments of the policy may be relevant to optimize the overall efficiency of the policy.